Analysis of Factors Influencing the Decision to Purchase Electric Motorcycles (Case Study in Padang City) - Malik, Mirza A; Setiawan, Fadli (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The introduction of electric vehicles (EV) in Indonesia still requires time due to the low public interest. Previous studies have shown that the intention to purchase EVs is influenced by environmental awareness and product comfort, while other factors such as brand, dealers, and payment methods also play a role. This study aims to measure the influence of product attributes and consumer behavior on the purchase decision of electric motorcycles in Padang City using both qualitative and quantitative descriptive methods. Data were collected through interviews and questionnaires with Stratified Random Sampling techniques, then analyzed using SMART PLS 3.0 and Path Analysis. The results show that product attributes, including brand, price, quality, features, and design, have a positive and significant effect on the purchase decision. However, consumer behavior, which includes cultural, social, personal, and psychological aspects, although positively influential, does not have a significant direct impact on the electric motorcycle purchase decision in Padang City.